(untitled) (Scientific journal of the Fergana State University, 2025)
This article explores the implementation of task-based language teaching (TBLT) strategies in English as a Foreign Language (EFL) classes in higher education institutions. It examines the peculiarities of the method, the necessity for researching its implementation, as well as strategies and models for integrating TBLT. Results from experiments conducted in four higher education institutions are presented.